Rapid Loss of Relativistic Electrons by EMIC Waves in the Outer Radiation Belt Observed by Arase, Van Allen Probes, and the PWING Ground Stations - S. Kurita; Y. Miyoshi; K. Shiokawa; N. Higashio; T. Mitani; T. Takashima; A. Matsuoka; I. Shinohara; C. A. Kletzing; J. B. Blake; S. G. Claudepierre; M. Connors; et al. (Geophysical Research Letters)
Abstract There has been increasing evidence for pitch angle scattering of relativistic electrons by electromagnetic ion cyclotron (EMIC) waves. Theoretical studies have predicted that the loss time scale of MeV electrons by EMIC waves can be very fast, suggesting that MeV electron fluxes rapidly decrease in association with the EMIC wave activity. This study reports on a unique event of MeV electron loss induced by EMIC waves based on Arase, Van Allen Probes, and ground‐based network observations. Arase observed a signature of MeV electron loss by EMIC waves, and the satellite and ground‐based observations constrained spatial‐temporal variations of the EMIC wave activity during the loss event. Multisatellite observation of MeV electron fluxes showed that ~2.5‐MeV electron fluxes substantially decreased within a few tens of minutes where the EMIC waves were present. The present study provides an observational estimate of the loss time scale of MeV electrons by EMIC waves.